Pengaruh Kualitas Produk, Citizen Brand dan Promosi terhadap Keputusan Pembelian AQUA Galon di Semarang Barat - Taruli Sibarani; Apriatni Endang Prihartini; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of product quality, brand citizen, and promotion on purchase decisions AQUA gallon in Semarang barat. Type of research used in this research is explanatory research with 100 respondents drawn using purposive sampling technique. The method of analysis used in this study using linear regression analysis using SPSS for windows. The result of research showed that quality of product has a significant effect (partial) on purchase decisions AQUA gallons in Semarang barat  18.2 percent. Citizen brand has a significant effect (partial) on purchase decisions AQUA gallon in Semarang barat  37.7 percent. Promotion also has a significant effect (partial) on purchase decisions AQUA Gallons in Semarang barat 8.6 percent. Quality of product, citizen brand and promotion simultaneously have the effect on purchase decisions AQUA Gallons in Semarang 37.9 percent